A Selective Neutraligand for CXCL12/SDF-1α With Beneficial Regulatory Functions in MRL/Lpr Lupus Prone Mice - Schall, Nicolas; Daubeuf, François; Marsol, Claire; Gizzi, Patrick; Frossard, Nelly; Bonnet, Dominique; Galzi, Jean-Luc; Muller, Sylviane (Frontiers in Pharmacology, 2021)
Dysregulation of CXCL12/SDF-1-CXCR4/CD184 signaling is associated with inflammatory diseases and notably with systemic lupus erythematosus. Issued from the lead molecule chalcone-4, the first neutraligand of the CXCL12 chemokine, LIT-927 was recently described as a potent analogue with improved solubility and stability. We aimed to investigate the capacity of LIT-927 to correct immune alterations in lupus-prone MRL/lpr mice and to explore the mechanism of action implemented by this small molecule in this model. We found that in contrast to AMD3100, an antagonist of CXCR4 and agonist of CXCR7, LIT-927 reduces the excessive number of several B/T lymphocyte subsets occurring in the blood of sick MRL/lpr mice (including CD3+/CD4-/CD8-/B220+ double negative T cells). In vitro, LIT-927 downregulated the overexpression of several activation markers on splenic MRL/lpr lymphocytes. It exerted effects on the CXCR4 pathway in MRL/lpr CD4+ T spleen cells. The results underline the importance of the CXCL12/CXCR4 axis in lupus pathophysiology. They indicate that neutralizing CXCL12 by the neutraligand LIT-927 can attenuate hyperactive lymphocytes in lupus. This mode of intervention might represent a novel strategy to control a common pathophysiological mechanism occurring in inflammatory diseases.